2016
DOI: 10.1149/2.0191613jes
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Polymer Electrolyte Membrane Fuel Cells Operated at Subfreezing Temperatures

Abstract: The structure, composition, and interfaces of membrane electrode assemblies (MEA) and gas-diffusion layers (GDLs) have a significant effect on the performance of single-proton-exchange-membrane (PEM) fuel cells operated isothermally at subfreezing temperatures. During isothermal constant-current operation at subfreezing temperatures, water forming at the cathode initially hydrates the membrane, then forms ice in the catalyst layer and/or GDL. This ice formation results in a gradual decay in voltage. High-frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 73 publications
(122 reference statements)
2
9
0
Order By: Relevance
“…The fitting results shown in Figure 2d reveal that the ohmic resistance and R ct remains nearly constant, while R mt increases 20 times rapidly in the latter stage. This observation is consistent with Mukundan et al 15,16 The dynamic PEIS (H 2 /N 2 ) results during cold start are shown in Figure 3. The catalyst layer behaves as a blocking porous electrode at the voltage higher than 0.1 V and a porous electrode with faradaic reactions at the OCV.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The fitting results shown in Figure 2d reveal that the ohmic resistance and R ct remains nearly constant, while R mt increases 20 times rapidly in the latter stage. This observation is consistent with Mukundan et al 15,16 The dynamic PEIS (H 2 /N 2 ) results during cold start are shown in Figure 3. The catalyst layer behaves as a blocking porous electrode at the voltage higher than 0.1 V and a porous electrode with faradaic reactions at the OCV.…”
Section: Resultssupporting
confidence: 92%
“…The last piece of CV was measured after ice formation, which is evidenced by a sharp potential drop. The five CV curves almost coincide with each other and the ECSA values vary within 4%, indicating that ice formation does not reduce the TPI, which is consistent with Mukundan et al 15,16 but contradicts with Ge et al 14 This discrepancy may be ascribed to the fact that different samples were used in these experiments. Ge et al 14 employed a homemade CCM incorporating an 18 μm Gore-Select membrane while Mukundan et al 15,16 employed a Gore PRIMEA 57 series MEA.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations